?RESPONSE OF SOME COTTON VARIETIES TO COTTON LEAF CURL VIRUS (Biological Sciences - PJSIR, 1995)
Incidence of cotton leaf curl and yield of seed cotton in six varieties/strains of upland cotton viz; CIM-109, CIM-240, CIM -243, CIM -262, MS-84 and S-12 were recorded at nine locations. Leaf curl infestation was minimum in CIM -240 followed by CIM-I09. Based on average at 9 locations, CIM-240 gave the highest yield closely followed by CIM-I09.